2012
DOI: 10.1590/s0102-695x2012005000106
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive extracts and chemical constituents of two endophytic strains of Fusarium oxysporum

Abstract: Abstract:Ethyl acetate extracts of cultures grown in liquid Czapek and on solid rice media of the fungal endophyte Fusarium oxysporum SS46 isolated from the medicinal plant Smallanthus sonchifolius (Poepp.) H. Rob., Asteraceae, exhibited considerable cytotoxic activity when tested in vitro against human cancer cells. Chromatographic separation yielded anhydrofusarubin (1) and beauvericin (2) that were identified based on their 1 H and 13 C NMR data. Compounds 1 and 2 showed the strongest cytotoxic activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…22 Antimicrobial Anti-inflammatory 23 likewise Methyl Streate has already been reported as antidiarrheal. 25 Therefore, it is concluded that Coptis teeta need protection, propagation and further studies for the welfare of ecosystem and mankind.…”
Section: Resultsmentioning
confidence: 99%
“…22 Antimicrobial Anti-inflammatory 23 likewise Methyl Streate has already been reported as antidiarrheal. 25 Therefore, it is concluded that Coptis teeta need protection, propagation and further studies for the welfare of ecosystem and mankind.…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation of the endophyte was carried out using a procedure by Nascimento et al (2012) with slight modification. The solid-state fermentation was carried out in 21, 500 ml Erlenmeyer flasks containing 90 g of rice in 90 ml of distilled water per flask which were twice autoclaved at 120°C for 40 min.…”
Section: Fermentation and Extraction Of Secondary Metabolitesmentioning
confidence: 99%
“…The resulting mycelia were extracted with 300 ml of methanol for 48 h to yield the crude mycelial extracts. The production of natural beauvericin was analyzed by high performance liquid chromatography coupled with a photodiode array detector (HPLC-PDA), by comparison with a previously isolated beauvericin standard (Nascimento et al, 2012). HPLC analyses were carried out by a Shimadzu ® HPLC with LC-6AD pumps, a SCL-10AVP system controller, a diode array detector UV/VIS SPD-M10AVP and RID-10A, SIL-10AF autosampler, and Class VP software.…”
Section: Extraction and Analyses By Hplc And Maldi-tof/tofmentioning
confidence: 99%
“…The endophytic fungus Fusarium oxysporum SS46, isolated from the host plant Smallanthus sonchifolius (Gallo et al, 2009), is a producer of the cyclohexadepsipeptide beauvericin (Nascimento et al, 2012). Beauvericin has antibiotic, antifungal, insecticidal, antimycobacterial, antiplasmodial, and nematicidal properties, and also inhibits angiogenesis, cell migration, and cancer cell proliferation (Xu et al, 2007;Zhan et al, 2007;Zhang et al, 2007;Xu et al, 2009;Shimada et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation